(untitled) (مجلة الواحات للبحوث والدراسات, 2023)
ملخص: إنّ أدب الفكاهة مثير للمتعة، وقد ورد في الأدب الرّسمي على مرّ العصور، إلاّ إنّ محل دراستنا تكمن في مدى تواجد الأدب الفكاهي في الأدب الشّعبي الجزائري، ونهدف من خلال ذلك إلى إبراز حس الفكاهة، وما يتضمّنه من الطّرافة والظّرف لدى الشّعب الجزائري. ومن هذا المنطلق جاءت نطرح السّؤال الآتي: هل توفّر الأدب الشّعبي الجزائري على الحس الفكاهي؟ اعتمدنا في عرض بحثنا منهجيّة قائمة على ذِكر أهم العناوين المرتبطة بالموضوع، فبدأنا بذكر الجانب المفاهيمي للحس الفكاهي، ثمّ أشرنا إلى هذا الأدب في التراث العربي القديم، لننتقل بعدها إلى الحس الفكاهي في الأدب الشّعبي، وفصّلنا فيه من خلال عرضه وفقًا للفنون الأدبيّة الشّعبيّة. ومن النّتائج المتوصّل إليها من خلال البحث؛ وفرة الحس الفكاهي في الأدب الشّعبي الجزائري، واختلاف مظاهره، بين الطّرفة، والحيلة، والسّخرية، والتهكّم، فكلّها دارجة في أدبنا الشّعبي الجزائري، ممّا يعكس روح الدّعابة لدى الشّعب الجزائري. كلمات دالة: حس؛ فكاهة؛ أدب؛ شّعب؛ جزائر. Abstract: Humor is interesting. It has been written in official literature throughout the ages. We study the extent to which comic literature is present in Algerian popular literature. We aim to highlight the sense of humor, the humor it contains in the Algerian people. From it came the research problem as follows: Does Algerian folk literature offer a sense of humor?. In our presentation, we used a methodology based on the most relevant headings; The conceptual side of humor, this literature in ancient Arabic heritage, the sense of humor in folk literature, through popular literary arts. research results; The abundance of humor in Algerian popular literature, and the different manifestations of it, are: humor, mockery and sarcasm. They are all found in our Algerian folk literature, reflecting the sense of humor among the Algerian people. Keywords: sense; humor; literature; People; Algeria.